Factors influencing TikTok engagement behaviors in China: An examination of gratifications sought, narcissism, and the Big Five personality traits. (August 2021) - Meng, Keira Shuyang; Leung, Louis
Abstract: As an over-the-top (OTT) and non-subscription-based video-on-demand media service, mobile short-form video application (e.g., TikTok or Douyin) is a free video-sharing social networking service (SNS) distributing short-form video content to smartphones, smart TVs, and tablets. This study investigates the roles of gratifications-sought, narcissism, and personality traits in TikTok engagement behaviors (i.e., contribution, enhancement, and creation) in China. Data were gathered from a sample of 526 TikTok users through an online questionnaire survey in 2020. Factor analysis confirmed nine gratifications sought: escape, fashion, entertainment, information seeking, money making, sociability seeking, navigability, modality, and interactivity. In particular, extraverts and people with the quality of being vain were most active in the contributing, enhancing, and creating TikTok engagement behaviors. The results also show that exhibitionists and people who are more open to new experiences were found to create more, while narcissists with an attitude of entitlement also engaging strongly in giving likes, commenting, forwarding TikToks, and following others. Theoretical and practical implications are also discussed. Highlights: Explored how gratifications-sought, narcissism, and personality traits influence use intensity and usage patterns of TikTok. Interactivity, modality, navigability, entertainment, entitlement in narcissism, and age were related to TikTok use. Extraverts and those to be vain were most active in the contribution, enhancement, and creation functions. Exhibitionists and people who are more open to new experiences would engage more. Narcissists with an attitude of entitlement reacted strongly in giving likes, commenting, forwarding, and following others.